Understanding youth in the global economic crisis - France, Alan (Policy Press, 2016)
Alan France presents new and original analysis of social policy responses to the economic crisis to examine the effects on young people's relationship with the life course. Drawing on international case studies from the UK, Spain, Norway, Japan, Australia, New Zealand and Canada, the book will consider how 'youth' and the 'youth question' within social policy has been (and is) changing as a result of global disruption to international capital.